The Relationship Between Sanitation Conditions and Community-Based Total Sanitation Behavior on the Incidence of Diarrhea in Toddlers at UPT Puskesmas Namo Terasi, Sei Bingai Langkat - Zulia Wirdani Putri Nst; Meutia Nanda (PROMOTOR, 2023)
Diarrhea is a global problem found throughout the world. Based on data from the Indonesian Health Service in 2020, in Indonesia there were 843 babies and 270 adults who experienced diarrhea. There are five pillars in STBM, namely stopping open defecation, washing hands with soap, managing household drinking water and food, securing household waste and safeguarding household liquid waste. The aim of this study was to determine the relationship between STBM conditions in general and the incidence of diarrhea. This research is a quantitative study with a cross-sectional design and a sample size of 71 respondents. Statistical tests use chi-square. The results of this study show that there is a relationship between CTPS behavior (P=0.001), drinking water and food management behavior (p=0.009) and waste management (p=0.041) with the incidence of diarrhea. However, the results of this study showed that there was no relationship between defecation behavior (P=0.825) and liquid waste management (p=0.510) with the incidence of diarrhea. The conclusion of this research is that there is a significant relationship between STBM behavior and the incidence of diarrhea in toddlers seen from the pillar aspects of hand washing behavior with soap, waste management and eating and drinking management behavior.